Placebo effects of repetitive transcranial magnetic stimulation on negative symptoms and cognition in patients with schizophrenia spectrum disorders: a systematic review and meta-analysis - Wang, Mingqi; Lu, Shensen; Hao, Lu; Xia, Yifei; Shi, Zhenchun; Su, Lei (Frontiers in Psychiatry, 2024)
Background: Negative symptoms and cognitive impairments are highly frequent in schizophrenia spectrum disorders (SSD), associated with adverse functional outcomes and quality of life. Repetitive transcranial magnetic stimulation (rTMS) has been considered a promising therapeutic option in SSD.However, placebo effects of rTMS on these symptoms remained unclear.Objective: To investigate placebo effects of rTMS on alleviating negative symptoms and cognitive impairment in patients with SSD and to explore potential moderators.We systematically searched five electronic databases up to 15 July 2023. Randomized, double-blind, sham-controlled trials investigating effects of rTMS on negative symptoms or cognition in patients with SSD were included. The pooled placebo effect sizes, represented by Hedges' g, were estimated using the random-effects model. Potential moderators were explored through subgroup analysis and meta-regression.Results: Forty-four randomized controlled trials with 961 patients (mean age 37.53 years; 28.1% female) in the sham group were included. Significant low-to-moderate pooled placebo effect sizes were observed for negative symptoms (g=0.44, p<0.001), memory (g=0.31, p=0.010), executive function (g=0.35, p<0.001), working memory (g=0.26, p=0.004), and processing speed (g=0.36, p=0.004). Subgroup analysis indicated that placebo effects were affected by sham stimulation methods, rTMS targeting approaches, and stimulation frequency.Conclusions: Placebo effects of rTMS on negative symptoms and cognition in patients with SSD are significant in a small-to-moderate magnitude, which might be mediated by rTMS parameters. Our findings will provide new insights for practitioners to further optimize and establish standardized rTMS protocols for future RCTs tackling cardinal symptoms in SSD.